Placement decisions and disparities among Aboriginal children: Further analysis of the Canadian incidence study of reported child abuse and neglect part A: Comparisons of the 1998 and 2003 surveys - Fallon, B., Chabot, M., Fluke, J., Blackstock, C., MacLaurin, B., & Tonmyr, L. (Child Abuse & Neglect, 2013)
Fluke et al. (2010) analyzed Canadian Incidence Study on Reported Child Abuse and Neglect (CIS) data collected in 1998 to explore the influence of clinical and organizational characteristics on the decision to place Aboriginal children in an out-of-home placement at the conclusion of a child maltreatment investigation. This study explores this same question using CIS data collected in 2003 which included a larger sample of Aboriginal children and First Nations child and family service agencies. The decision to place a child in an out-of-home placement was examined using data from the Canadian Incidence Study of Reported Child Abuse and Neglect-2003 and a reanalysis of CIS-1998 data ( Fluke et al., 2010). The CIS-2003 dataset includes information on nearly 12,000 child maltreatment investigations from the time of report to case disposition. The CIS-2003 also captures information on the characteristics of investigating workers and the child welfare organizations for which they work. Multi-level statistical models were developed to analyze the influence of clinical and organizational variables using MPlus software. MPlus allows the use of dichotomous outcome variables, which are more reflective of decision-making in child welfare and facilitates the specific case of the logistic link function for binary outcome variables under maximum likelihood estimation. Final models revealed the proportion of investigations conducted by the child welfare agency involving Aboriginal children was a key single agency level predictor of the placement decision. Specifically, the higher the proportion of investigations of Aboriginal children, the more likely placement was to occur. Contrary to the findings in the first paper (Fluke et al., 2010), individual Aboriginal status also remained significant in the final model at the first level. Further analysis needs to be conducted to further understand individual and organizational level variables that may influence decisions regarding placement of Aboriginal children. There is also a ...